Characteristics and outcomes of patients with grill-related Burn injuries admitted to the Cologne Burn Center, Germany. Issue 5 (August 2020) - Al Shamsi, Mustafa; Fuchs, Paul Christian; Perbix, Walter; Grigutsch, Daniel; Daniels, Marc; Schulz, Alexandra; Schiefer, Jennifer Lynn
Highlights: This retrospective study compared grill-related and other burn injuries. Most cases involved men with an average age of 34 years. Most grill-related burn injuries occurred in summer and spring. The upper limb and head were most commonly affected. Grill-related injuries required a less aggressive approach than other fire injuries. Abstract: Background: Grilling has become increasingly common in Germany. Although grilling is considered a non-negligible household burn hazard, few reports have assessed this type of injury. This study aimed to determine the patterns and characteristics of grill-related burn injuries and to compare these with other types of burn injuries. Methods: This retrospective observational study included all grill-related burn injuries admitted to Cologne Merheim Burn Center during 1989–2017. The collected data were analyzed descriptively and compared statistically with other fire injuries. Results: Of 1706 cases admitted with fire injuries during the study period, 160 (∼10%) involved grill-related injuries. Most cases (85%) involved men, with an average age of 34 years. Moreover, 48% and 38% of cases occurred in summer and spring, respectively. The most common mechanism of injury was ignition via fluid accelerant. The upper limb was the most commonly affected body part, followed by the head. Statistical analyses revealed that grill-related injuries were associated with a lower mean age and total body surface area, shorter in-hospital stay, and fewer complications than the other fire injury group. Conclusion: Grill-related injuries are a relatively common cause of admission to the Cologne Burn Center. Although grill-related injuries underwent a less aggressive approach than the other investigated fire injuries, the former represent a public health concern because they mainly affect the upper body, with both psychologic and aesthetic consequences. We recommend a German nationwide multi-centric study of the patterns and characteristics of burn injury.